How will we manage acute HCV in men having sex with men in the era of all oral therapy?. Issue 1 (21st October 2014) - Boesecke, C.; Rockstroh, J. K.
Summary: With the advent of direct‐acting antivirals (DAAs), the treatment of chronic hepatitis C virus (HCV) infection (CHC) has been revolutionized. Modern interferon‐ and potentially also ribavirin‐free combinations consisting of 2 or 3 direct‐acting antivirals (DAA) promise sustained virological response rates (SVR) of above 90%. This coincides with much shorter treatment durations and a much more favorable toxicity profile. Some DAAs even work across all HCV genotypes (pangenotypic) [ BMJ, 349, 2014, g3308]. And lastly, HCV treatment in HIV‐coinfected patients will no longer differ from HCV‐monoinfected patients as response rates under DAA in the setting of HCV–HIV coinfection have been as good as in HCV‐monoinfected patients [ J Hepatol, 61, 2014, 373]. Only drug–drug interactions with the new DAAs and concomitant antiretroviral therapy have to be accounted for due to shared metabolization pathways via the cytochrome p450 system.